2016
DOI: 10.1007/s13317-016-0090-1
|View full text |Cite
|
Sign up to set email alerts
|

Structure and activation of the TSH receptor transmembrane domain

Abstract: PurposeThe thyroid-stimulating hormone receptor (TSHR) is the target autoantigen for TSHR-stimulating autoantibodies in Graves’ disease. The TSHR is composed of: a leucine-rich repeat domain (LRD), a hinge region or cleavage domain (CD) and a transmembrane domain (TMD). The binding arrangements between the TSHR LRD and the thyroid-stimulating autoantibody M22 or TSH have become available from the crystal structure of the TSHR LRD–M22 complex and a comparative model of the TSHR LRD in complex with TSH, respecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(6 citation statements)
references
References 92 publications
0
5
0
1
Order By: Relevance
“…Thyrotrophic hormone (TSH, thyroid-stimulating hormone) is a heterodimeric glycoprotein with a molecular weight of 28 kDa, composed of two subunits: α (encoded by the gene on chromosome 6) and specific β (encoded by the gene on chromosome 1). TSH receptors (TSHR, thyrotropin-secreting hormone receptors) belong to membrane receptors acting through the class A G protein complex (GPCR, G protein-coupled receptors) [65,66]. It has been found that the cell energy deficit correlates with a decrease in TSH synthesis and secretion [77,78].…”
Section: Thyrotrophic Hormone (Tsh)mentioning
confidence: 99%
“…Thyrotrophic hormone (TSH, thyroid-stimulating hormone) is a heterodimeric glycoprotein with a molecular weight of 28 kDa, composed of two subunits: α (encoded by the gene on chromosome 6) and specific β (encoded by the gene on chromosome 1). TSH receptors (TSHR, thyrotropin-secreting hormone receptors) belong to membrane receptors acting through the class A G protein complex (GPCR, G protein-coupled receptors) [65,66]. It has been found that the cell energy deficit correlates with a decrease in TSH synthesis and secretion [77,78].…”
Section: Thyrotrophic Hormone (Tsh)mentioning
confidence: 99%
“…Thyroid-stimulating hormone receptor (TSHR) is a member of the glycoprotein hormone receptor (GPHR) subfamily that belongs to the leucine-rich repeat-containing GPCR family (LGR), which includes also follicle-stimulating hormone (FSH), luteinising hormone (LH), and human chorionic gonadotropin (hCG) receptors [19,20]. The TSHR gene is located on chromosome 14q31.1 and spans 190 778 bp, which contains 10 exons [21].…”
Section: Thyroid-stimulating Hormone Receptor (Tshr)mentioning
confidence: 99%
“…Receptor hormonu tyreotropowego jest członkiem podrodziny receptorów hormonów glikoproteinowych (GPHR, glycoprotein hormone receptor), należącej do rodziny receptorów sprzężonych z białkiem G, zawierających powtórzenia bogate w leucynę (LGR). Rodzina ta obejmuje także receptory hormonu folikulotropowego (FSH, follicle-stimulating hormone), luteinizującego (LH, luteinising hormone) i ludzkiej gonadotropiny kosmówkowej (hCG, human chorionic gonadotropin) [19,20]. Gen kodujący TSHR znajdujący się na chromosomie 14q31.1, składa się z 190 778 par zasad i 10 egzonów [21].…”
Section: Receptor Hormonu Tyreotropowego (Tshr)unclassified
“…Gly132 is located in the extracellular leucine-rich repeat (LRR) domain of the TSHR. The large concave surface of the TSHR LRR represents the site of interaction between TSHR and TSH, as well as TSHR and its autoantibodies [ 31 ]. Glycine 132 is located on the β strand of the fifth LRR repeat, between residues Phe130 and Phe134, which interact with Lys91 and Tyr88, respectively, in the TSH–TSHR model complex (and with Pro97 in the thyroid-stimulating autoantibody M22–TSHR complex) [ 32 ].…”
Section: Description Of Casesmentioning
confidence: 99%